2016
DOI: 10.3111/13696998.2016.1151432
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of nivolumab for the treatment of second-line advanced squamous NSCLC in Canada: a comparison of modeling approaches to estimate and extrapolate survival outcomes

Abstract: Background Lung cancer is the most common type of cancer in the world and is associated with significant mortality. Nivolumab demonstrated statistically significant improvements in progression-free survival (PFS) and overall survival (OS) for patients with advanced squamous non-small cell lung cancer (NSCLC) who were previously treated. The cost-effectiveness of nivolumab has not been assessed in Canada. A contentious component of projecting long-term cost and outcomes in cancer relates to the modeling approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 25 publications
0
72
1
Order By: Relevance
“…A potential for inherent bias in a partitioned survival model has recently been raised by hypothetical modelling and simulated data [39,40]. However, an empirical analysis using real-world data by Goeree et al [41] found that the partitioned survival model and the Markov model produced similar ICER estimates in advanced NSCLC, confirming the structural validity of the partitioned survival approach in the current analysis [41]. Still, uncertainty is inherent in the survival projections/extrapolation of PFS and OS to model beyond the trial period.…”
Section: Discussionmentioning
confidence: 99%
“…A potential for inherent bias in a partitioned survival model has recently been raised by hypothetical modelling and simulated data [39,40]. However, an empirical analysis using real-world data by Goeree et al [41] found that the partitioned survival model and the Markov model produced similar ICER estimates in advanced NSCLC, confirming the structural validity of the partitioned survival approach in the current analysis [41]. Still, uncertainty is inherent in the survival projections/extrapolation of PFS and OS to model beyond the trial period.…”
Section: Discussionmentioning
confidence: 99%
“…Similar economic evaluations of nivolumab for the treatment of various tumors types have consistently come to the same conclusion. An economic evaluation of nivolumab for the treatment of NSCLC in Canada resulted in an ICER of $151,560 CAD per QALY compared with docetaxel . Similarly, in Switzerland, an evaluation of nivolumab compared with docetaxel for the treatment of advanced NSCLC resulted in an ICER of 177,478 Swiss francs ($245,962 CAD) per QALY .…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness studies suggest that the costs of many new treatments, including multiplex genomic testing, 250 novel targeted kinase inhibitors 251 and checkpoint inhibitors, are above traditional willingness-to-pay thresholds. [252][253][254] Each jurisdiction must determine its own willingness to pay for new treatments, which varies across countries and health care systems. Given that severe financial toxicity is recognized as a potential predictor of early mortality in lung and other cancers, 255 implementing strategies to ensure affordable access to treatment has never been more important for patients with lung cancer and their families.…”
Section: Mesotheliomamentioning
confidence: 99%